Finland : 2007 Article IV Consultation; Staff Report; Staff Statement and Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Finland. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This 2007 Article IV Consultation highlights that growth in Finland has outpaced the euro area average. Inflation is among the lowest in the European Union, and the external current account and general government budget are both comfortably in surplus. The labor market has improved markedly since 2005, with rising participation rates and comparatively strong employment growth. The unemployment rate has dipped below the euro area average, and hovers near estimates of the structural unemployment rate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet